Mechanical and physical properties of chalk and impacts on mining operations and slope designs - Ebeling, P; Iwanoff, A (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Chalk occurs in northern Europe from the southern UK to eastwards deep into Russia. It is exploited as an industrial mineral for a large variety of uses. From the examples of three different chalk mining operations, it is shown that although geologically and geochemically quite similar, all three deposits have very different physical and geomechanical properties which in turn have impacts on slope designs as well as mining method, mine planning and equipment selection.
Keywords: weak rocks